Determinants of postpartum depression among mothers in Debre Tabor town, North-central, Ethiopia: Community-based unmatched case-control study - Dagnaw, Fentaw Teshome; Addis, Wondimnew Desalegn; Tesfa, Desalegn; Desale, Aragaw Tesfaw; Issa, Nurayine Abubeker; Belachew, Yismaw Yimam; Yitbarek, Getachew Yideg; Belay, Alebachew Taye; Chanie, Ermias Sisay; Hailemeskel, Habtamu Shimels (Frontiers in Global Women's Health, 2022)
Background: Postpartum depression is a non-psychotic depressive disorder of variable severity and it can begin as early as two weeks after delivery and can persist indefinitely if it is left untreated. In Ethiopia the prevalence of postpartum depression was high. There is a dearth of literature to determine factors associated with postpartum depression in Ethiopia, specifically in the study area. Objective: This study aimed to determine factors associated with postpartum depression among mothers in Debre Tabor Town, Northcentral, Ethiopia, 2020. Method: A community-based unmatched case-control study was conducted among mothers who are living in Debre Tabor Town and who fulfilled the inclusion criteria. The postpartum mother was selected using a simple random sampling technique from the listed sampling frame at the health post. Then, cases and controls were interviewed until the sample size was fulfilled by using consecutively. Data was entered into the EPI data version 4.6 and then imported and analyzed using SPSS version 25. Descriptive statistics of different variables were done by cross-tabulation. Binary logistic regression was used to assess the determinant factors with the outcome variable. A P-value of < 0.05 was considered to declare statistical significance. Results: A total of 308 postnatal mothers who are living in Debre Tabor Town were included, with a 97.5% response rate. History of substance use in the last three months (AOR: 6.47, 95% CI; 2.61, 15.74), current baby illness (AOR: 3.9, 95% CI; 1.5, 10.12), marital dissatisfaction (AOR: 2.41, 95% CI; 1.22, 4.75), unplanned current pregnancy (AOR: 3.46, 95% CI; 1.32, 9.12), breastfeeding (AOR: 0.22, 95% CI; 0.09, 0.55) were independent factors affecting the occurrence of PPD. Conclusions: This study revealed that history of substance use in the last three months, current baby illness, marital satisfaction, planned current pregnancy, and breastfeeding were associated with postpartum depression. Health care providers working in maternal and child health clinics and health extension workers should give special attention to postpartum mothers who have a history of substance use, current baby illness, has an unplanned pregnancy, nonbreastfeeding mothers and have poor marital satisfaction.